Effectiveness of Psychological Contract at Workplace & Organizational Commitment : A Case Study - Al-Fannoush, Yassin Marouf (2013)
The research objective was to develop model to measure the effectiveness of psychological contracts for managerial level employees through involving factors derived the psychological contract and are likely to influence commitment of the employees, The psychological contract is the unwritten implicit contract that forms in the minds of employees and contains the obligations and expectations that they believe exists between themselves and the organization. Although the contribution the research makes to the field of knowledge may be limited, it does provide some validation of existing measures of the psychological contract, developed in other studies using different samples. The present findings increase our knowledge of the content of the psychological contract for managers. Additionally, a methodological framework has been established for continuing research into the content of psychological contracts, including an examining of the relationship between content and fulfillment, along with a structure measuring the impact of psychological contract on organizational commitment. The hypothesis was tested using qualitative method via surveying total of 160 employees representing four prominent banks institutions in Malaysia. We have measured the effect of four independent variables i.e. (Mutuality, Trust, Job Satisfaction, and Rewards) towards the dependent variable (Organization Commitment) in order to address the problem of high attrition rate existing in the Malaysian financial institutions. Some of the said variables showed a significant strong positive contribution towards commitment such as (Job Satisfaction & Trust), while others maintain significant moderate positive contribution towards organizational commitment such as (Mutuality & Rewards). However, outcomes vary from internal banks participants into local banks participants.